Pengembangan Produk Menggunakan Metode Agile Scrum - Haryono, Angelique Keyko; Adelia, Adelia (Maranatha University Press, 2025)
HiColleagues is an edutech startup company that focuses on IT services and education. With the increasing number of competitors in the edutech field, HiColleagues formed a Business Development division to ensure the business process runs well. One of the sub-divisions of Business Development is Product, which is in charge of developing HiColleagues products so that they can compete with competitors. The Product sub-division will develop HiColleagues products by creating documents as needed. All of these tasks will be done by implementing the Agile Scrum method where each task will be divided into several sprints and using Trello to document all tasks. By using the Agile Scrum method and utilizing Trello, all tasks can be completed according to the deadline and thoroughly documented.